2015
DOI: 10.1111/jpn.12316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sulphur amino acids and dietary electrolyte balance levels on performance, jejunal morphology, and immunocompetence of broiler chicks

Abstract: As alterations of dietary electrolyte balance (DEB) can influence amino acid metabolism via changes the ions incur in their configurations, performance and immunological responses of broiler chicks might be affected. So, the current study was carried out to investigate the effects of different levels of sulphur amino acids (SAA) and DEB on performance, jejunal morphology and immunocompetence of broiler chicks. A total of 360 1-day-old male Ross 308 broiler chicks were randomly assigned to nine experimental tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(84 reference statements)
0
6
1
Order By: Relevance
“…HERNANDEZ et al (2012) reported that plasma UA concentrations were not affected by increased levels of protein in the diet of broilers in the initial, growth and final phases. Results reported in this study for ALB disagree with the results of NIKOOFARD et al (2016), who showed that ALB levels increased significantly with the increase of crystalline methionine levels in the diet of male Ross 308 broilers at 42 days of age.…”
Section: -----------------------------------------------------------------------------------21 Days--------------------------------------contrasting
confidence: 99%
“…HERNANDEZ et al (2012) reported that plasma UA concentrations were not affected by increased levels of protein in the diet of broilers in the initial, growth and final phases. Results reported in this study for ALB disagree with the results of NIKOOFARD et al (2016), who showed that ALB levels increased significantly with the increase of crystalline methionine levels in the diet of male Ross 308 broilers at 42 days of age.…”
Section: -----------------------------------------------------------------------------------21 Days--------------------------------------contrasting
confidence: 99%
“…At the end of the experiment, two randomly selected hens from each cage were sacrificed to evaluate the effects of dietary treatments on intestinal cell morphology according to Nikoofard et al. (). Tissue samples were collected and a 2‐cm segment of jejunal region anterior to Meckel's diverticulum was excised for light microscopic observations.…”
Section: Methodsmentioning
confidence: 99%
“…Certain vitamins, for example, tocopherol [ 14 , 15 ] and retinol [ 16 ] have also been reported to decrease the abdominal fat content and enhance carcass mass of broilers. Concomitantly, dietary supplementation with minerals such as Mn [ 17 , 18 ], Zn [ 16 ], and S [ 19 ] was beneficial to decrease the abdominal fat deposition in broiler chickens. Moreover, supplementation of broiler feeds with Cu, Fe, Zn, and Mn improved meat quality of broilers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%